Dynamical variability of axisymmetric buoyant plumes. (26th January 2015) - Ezzamel, A.; Salizzoni, P.; Hunt, G. R.
Abstract: We present experimental measurements conducted on freely propagating, turbulent, steady thermal air plumes. Three plumes are studied with differing source conditions, ranging from jet-like, momentum flux dominated releases, to pure plume releases, characterised by a balance between the momentum, volume and buoyancy fluxes at the source. Velocity measurements from near the source to a height of tens of source diameters were made using particle image velocimetry (PIV), providing a high spatial resolution. Temperatures were measured with thermocouples. From these measurements, we investigate the vertical development of the plume fluxes and radial profiles of the mean velocity and temperature. These allow us to analyse the local self-preserving characteristics of the mean flow and to estimate the dependence with height of the plume Richardson number Γ . In addition, we analyse the similarity of one-point and two-point second-order velocity statistics, and we discuss the role of Γ on the vertical development of the bulk dynamical parameters of the plume, namely, the turbulent viscosity, the turbulent Prandtl number and the entrainment coefficient α_G . Comparison with previous experimental results and with estimates of the entrainment coefficient based on the mean kinetic energy budget allow us to conclude on the influence of Γ on the entrainment process and to explain possible physical reasons for the high scatter in estimates of α_G in the literature.